The Use of Botulinum A Toxin in Dysphagia. (2nd September 2014) - Amin, Nikul; Fu, Bertram; De Zoysa, Neil; Lew‐Gor, Simione
Abstract : Objectives: (1) Describe our experience with the use of botulinum A toxin (Botox) in a case series of patients with dysphagia with cricopharyngeal spasm on videofluoroscopy. (2) Systematic review of current literature. Methods: We present a case series of patients with dysphagia refractory to conventional conservative and medical treatment in whom we administered endoscopic injection of 100 mU of Botox into the cricopharyngeus by a single head and neck surgeon using the same technique. Eight patients with refractory dysphagia were treated with 100 mU of Botox injection into the cricopharyngeus. We excluded patients who previously had a surgical intervention to the upper esophagus or pharynx. The change in dysphagia after Botox administration was assessed using the Mayo Dysphagia Questionnaire‐30 before and approximately 2 weeks, 3 months, and 6 months after Botox administration and with pre‐ and post‐administration videofluoroscopies. Results: The Mayo Dysphagia Questionnaire‐30 scores improved significantly at all follow‐up stages postprocedure. This improvement is reflected in the post‐injection videofluoroscopy examinations. Conclusions: Dysphagia is often difficult to treat. It may be associated with upper esophageal sphincter dysfunction, where conventional treatment, including anti‐reflux medication and dilatation, may not be sufficient to provide symptomatic relief. A wide range of surgical interventions with associated morbidity have been described with varying success rates. Our method and experience with endoscopic injection of botulinum A toxin to the cricopharyngeus has shown to be an effective minimally invasive option in those who have been assessed as appropriate for the intervention.